2017
DOI: 10.1002/oa.2604
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Sex Prediction Using the Human Non‐Adult Auricular Surface of the Ilium in the Collection of Identified Skeletons of the University of Coimbra

Abstract: Sex estimation in non-adult skeletons is crucial in bioarchaeology and forensic anthropology. It was not extensively considered in the past, mainly because it was stated that the dimorphic osteological features were difficult to identify before adulthood. Over the past few years, this statement was disproved, and the study of numerous dimorphic non-adult skeletal traits was approached. This paper presents a new methodology that evaluates the auricular surface of the non-adult ilia. Several morphological and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
5
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 66 publications
(98 reference statements)
3
49
5
6
Order By: Relevance
“…Age at death was estimated based on dental eruption and development (AlQahtani, Hector, & Liversidge, ; Liversidge & Molleson, ), dental wear (Smith, ), and postcranial maturity (Scheuer & Black, ; Cardoso, , b). Because the pelvic bones were almost completely fused, sex estimation was done based on pelvic morphology (Bruzek, ; Luna, Aranda, & Santos, ). The mandible was also used (Ferembach, Schwidezky, & Stloukal, ).…”
Section: Methodsmentioning
confidence: 99%
“…Age at death was estimated based on dental eruption and development (AlQahtani, Hector, & Liversidge, ; Liversidge & Molleson, ), dental wear (Smith, ), and postcranial maturity (Scheuer & Black, ; Cardoso, , b). Because the pelvic bones were almost completely fused, sex estimation was done based on pelvic morphology (Bruzek, ; Luna, Aranda, & Santos, ). The mandible was also used (Ferembach, Schwidezky, & Stloukal, ).…”
Section: Methodsmentioning
confidence: 99%
“…Morphological methods have been criticized for high rates of inter‐observer error (Cardoso & Saunders, ; Luna, Aranda, & Santos, ; Sutter, 2008). Consequently, efforts have been made to develop metric techniques (Decker, Davy‐Jow, Ford, & Hilbelink, ; Krüger, L'abbe, & Stull, ; López‐Costas, Rissech, Trancho, & Turbón, ; Luna et al, ; Stull, L'Abbé, & Ousley, ; Wilson, Cardoso, & Humphrey, ; Wilson, MacLeod, & Humphrey, ). Even though reportedly more repeatable, metric methods require a good standard of skeletal preservation, which cannot be guaranteed, especially when dealing with the fragile remains of immature individuals.…”
Section: Introductionmentioning
confidence: 97%
“…Nonetheless, attempts to assign skeletal sex to immatures most frequently utilize the same skeletal traits known to be accurate for determining the sex of adults, including multiple features of the pelvis (Olivares & Aguilera, ; Rissech & Malgosa, ; Schutkowski, ; Sutter, ; Vlak, Roksandic, & Schillaci, ) and skull (Galdames, Matamala, & Smith, ; Loth & Henneberg, ; Molleson, Cruse, & Mays, ; Schutkowski, ). Morphological methods have been criticized for high rates of inter‐observer error (Cardoso & Saunders, ; Luna, Aranda, & Santos, ; Sutter, 2008). Consequently, efforts have been made to develop metric techniques (Decker, Davy‐Jow, Ford, & Hilbelink, ; Krüger, L'abbe, & Stull, ; López‐Costas, Rissech, Trancho, & Turbón, ; Luna et al, ; Stull, L'Abbé, & Ousley, ; Wilson, Cardoso, & Humphrey, ; Wilson, MacLeod, & Humphrey, ).…”
Section: Introductionmentioning
confidence: 99%
“…While it is posited that age plays a role in the expression of the auricular surface elevation , consequent to the widening of the female pelvis in puberty , the feature's expression has been assumed to present consistently across populations. However, adult studies have concluded that this trait may vary considerably between groups , and, more recently, researchers using the auricular surface for morphometric studies have cautioned that subadult pelvic traits may also be population specific. Regardless, sample variation has not been assessed for the auricular surface elevation in either adult or subadult samples.…”
mentioning
confidence: 99%
“…For more than 100 years, researchers have noted dimorphism in the subadult pelvis (1)(2)(3) in several of the metric and nonmetric traits found useful for adult sex estimation. More recent attempts to quantify and produce sex estimation methods based on these traits have met with limited success (4)(5)(6)(7)(8)(9)(10). Currently, no reliable method of analysis has been developed to capture subadult sex differences, although auricular surface elevation on the ilium, a dimorphic nonmetric trait in adults, has shown promise (5,7,8).…”
mentioning
confidence: 99%